2003
DOI: 10.1097/00002030-200301030-00001
|View full text |Cite
|
Sign up to set email alerts
|

A V106M mutation in HIV-1 clade C viruses exposed to efavirenz confers cross-resistance to non-nucleoside reverse transcriptase inhibitors

Abstract: V106M may be a signature mutation in clade C patients treated with EFV and may have the potential to confer high-level multi-NNRTI resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
177
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 275 publications
(191 citation statements)
references
References 12 publications
13
177
0
1
Order By: Relevance
“…Our present findings pertain to one specific PI. Wainberg and colleagues found that the V106M mutation confers cross-resistance to nonnucleoside reverse transferase inhibitors (4). This mutation appears frequently in subtype-C-infected patients treated with efavirenz and rarely in subtype-B-infected patients or in subtype-C-infected patients treated with nevirapine (4,9,20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our present findings pertain to one specific PI. Wainberg and colleagues found that the V106M mutation confers cross-resistance to nonnucleoside reverse transferase inhibitors (4). This mutation appears frequently in subtype-C-infected patients treated with efavirenz and rarely in subtype-B-infected patients or in subtype-C-infected patients treated with nevirapine (4,9,20).…”
Section: Discussionmentioning
confidence: 99%
“…Wainberg and colleagues found that the V106M mutation confers cross-resistance to nonnucleoside reverse transferase inhibitors (4). This mutation appears frequently in subtype-C-infected patients treated with efavirenz and rarely in subtype-B-infected patients or in subtype-C-infected patients treated with nevirapine (4,9,20). Moreover, in vitro studies of this group showed that the final drug concentration required for the development of resistance mutations conferring nonnucleoside reverse transferase inhibitors resistance was significantly lower for subtype C than for subtype B viruses and that resistant variants were fully selected more rapidly with the subtype C isolates than with the subtype B control (15,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some subtypes would develop resistance more frequently than subtypes A and B [9]; this could cause some natural nucleotide polymorphisms on specific codons [10] [11].…”
Section: Backgroundsmentioning
confidence: 99%
“…Des études effectuées récemment dans notre laboratoire, sur des isolats de sous-type C du VIH-1, ont montré la présence de polymorphismes naturels prédisposant à la résistance à certains INNTI ainsi qu'un profil de résistance spécifique à ce sous-type [25]. C'est le cas de la mutation Val106Met qui est sélectionnée par l'efavirenz (EFV) dans les souches de sous-type C et qui confère une résistance croisée aux trois INNTI commercialisés [26]. Une étude ougandaise plus récente (HIVNET 012) fait état d'une proportion plus importante de patientes porteuses de souches résistantes à la névirapine (NVP) chez les femmes infectées par le VIH-1 de sous-type D (36%) que chez celles infectées par le VIH-1 de sous-type A (19%) [27].…”
Section: La Thérapie Antirétroviraleunclassified